INFORMATION ABOUT THE SCIENCE OF "ILM AL-KHANDAS" IN THE WORKS OF ABU NASR FARABI (Academicia Globe: Inderscience Research, 2022)
The article provides information about the famous Central Asian scholar Abu Nasr al-Farabi in the IX-X centuries. Among the scientific treatises and manuscripts he wrote in several fields of science were manuscripts in mathematics, especially geometry, which at that time were called ilm al-handasa. The article provides information on these manuscripts, concepts and issues related to geometric constructions. It is recommended to use this information in the study of the history of modern graphic sciences and in solving problems.